Comparison of anthropometric, training, physiological parameters and performance between elite and non-elite Indian archers-An Indoor shooting analysis - Sharma, D.; Guru, C.; Mahajan, U.; Krishnan, A. (40th Annual Conference of Indian Association of Sports medicineAt: Bengaluru, India, 2019)
Background & Aim: Anthropometric, sports training and physiological parameters affect the performance of athletes. Identification of the key factors that influence shooting performance among Indian archers would provide valuable inputs to the coaches in terms of planning and monitoring of sports training. To ascertain this, a study was conducted, with an aim of comparison of these parameters and performance between Elite and Non-Elite Archers in a Sports Institute. Method: A total of Thirty-three archers including16 elite archers and 17 non-elite archers who volunteered (Age: 21.8 ± 5.5 years, Experience: 7.8 ± 5.6 years) shot 60 arrows each in two sessions of 30 arrows in a standard Indoor Archery hall. Recording of anthropometric data, sports age, physiological parameters and score were done. Pearson's Chi-Square test and multiple pair-wise comparison using Bonferroni corrections were used for statistical analysis. Parameters were expressed as Mean ± SD and statistical significance was set at p < 0.05.